The common law employment relationship : a comparative study - Anderson, Gordon (Edward Elgar Publishing, 2017)
The contract of employment provides in many jurisdictions the legal foundation for the employment of workers. This book examines how the development of the common law under the influence of contemporary social and economic pressures has caused this contract to evolve. International employment law experts provide a comparative study of the contract of employment across three closely related common law jurisdictions: the UK, Australia and New Zealand. Adopting a thematic approach, they analyse the key facets of the common law of employment such as who is an employee, the implied duties of employees and the restraints on employee mobility. Examining the interaction between common law and domestic statutory law and the politics and labour relations systems, this book considers the legal variations for each jurisdiction and its response to new developments in employment. It addresses the capacity of the common law to respond to contemporary developments such as the 'gig' economy and the increasingly intrusive surveillance of employees, both at work and in their private lives. Insightful and contemporary, this book will appeal to students and scholars of employment and contract law as well as those studying comparative law more widely. Practitioners involved in employment policy or employment litigation will also benefit from the wealth of up-to-date knowledge on common law trends and developments.